Modulating O2 Reactivity in a Fungal Flavoenzyme - Hernández-Ortega, Aitor; Lucas, Fátima; Ferreira, Patricia; Medina, Milagros; Guallar, Victor; Martínez, Angel T. (The Journal of biological chemistry, 2011)
Aryl-alcohol oxidase (AAO) is a flavoenzyme responsible for activation of O2 to H2O2 in fungal degradation of lignin. The AAO crystal structure shows a buried active site connected to the solvent by a hydrophobic funnel-shaped channel, with Phe-501 and two other aromatic residues forming a narrow bottleneck that prevents the direct access of alcohol substrates. However, ligand diffusion simulations show O2 access to the active site following this channel. Site-directed mutagenesis of Phe-501 yielded a F501A variant with strongly reduced O2 reactivity. However, a variant with increased reactivity, as shown by kinetic constants and steady-state oxidation degree, was obtained by substitution of Phe-501 with tryptophan. The high oxygen catalytic efficiency of F501W, ∼2-fold that of native AAO and ∼120-fold that of F501A, seems related to a higher O2 availability because the turnover number was slightly decreased with respect to the native enzyme. Free diffusion simulations of O2 inside the active-site cavity of AAO (and several in silico Phe-501 variants) yielded >60% O2 population at 3–4 Å from flavin C4a in F501W compared with 44% in AAO and only 14% in F501A. Paradoxically, the O2 reactivity of AAO decreased when the access channel was enlarged and increased when it was constricted by introducing a tryptophan residue. This is because the side chain of Phe-501, contiguous to the catalytic histidine (His-502 in AAO), helps to position O2 at an adequate distance from flavin C4a (and His-502 Nϵ). Phe-501 substitution with a bulkier tryptophan residue resulted in an increase in the O2 reactivity of this flavoenzyme. Background: Oxygen activation by aryl-alcohol oxidase, a key step in lignin biodegradation, is investigated. Results: Mutation of Phe-501, forming a bottleneck in the access channel, strongly affects the oxygen kinetic constants. Conclusion: An aromatic side chain at this position helps oxygen to attain a catalytically relevant position near flavin C4a and catalytic residue His-502. Significance: The possibility to modulate the oxygen reactivity of related GMC oxidoreductases is demonstrated.